2011
DOI: 10.1111/j.1365-2958.2011.07873.x
|View full text |Cite
|
Sign up to set email alerts
|

cAMP‐CRP co‐ordinates the expression of the protein acetylation pathway with central metabolism in Escherichia coli

Abstract: SummaryLysine acetylation is a well-established posttranslational modification widely conserved and distributed in bacteria. Although multiple regulatory roles have been proved, little is known about its regulation. Here, we present evidence that the transcription of the Gcn5-like acetyltransferase YfiQ of Escherichia coli (proposed name: PatZ) is regulated by cAMP-CRP and its implications on acetate metabolism regulation. The acetate scavenging acetyl-CoA synthetase (Acs) is regulated at the transcriptional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 45 publications
3
102
0
Order By: Relevance
“…Since its discovery, it has been shown that RLA controls Acs and other members of the acyl-CoA synthetases via acetylation and that this regulatory mechanism of metabolism is present in prokaryotes and eukaryotes (29,176). Acetylation of Acs homologues by SePat homologues has also been demonstrated in E. coli (141,177), R. palustris (69), B. subtilis (30), Streptomyces spp. (31), and Mycobacterium spp.…”
Section: Discovery Of Rla In Prokaryotesmentioning
confidence: 99%
“…Since its discovery, it has been shown that RLA controls Acs and other members of the acyl-CoA synthetases via acetylation and that this regulatory mechanism of metabolism is present in prokaryotes and eukaryotes (29,176). Acetylation of Acs homologues by SePat homologues has also been demonstrated in E. coli (141,177), R. palustris (69), B. subtilis (30), Streptomyces spp. (31), and Mycobacterium spp.…”
Section: Discovery Of Rla In Prokaryotesmentioning
confidence: 99%
“…In prokaryotes, some acetyltransferases for protein acetylation have been investigated, including SePat in S. enterica (15), EcPatZ in E. coli (4), RpPat in Rhodopseudomonas palustris (16), MtKat in M. uberculosis, MsKat in M. smegmatis (6), and SlPatA in Streptomyces lividans (17). These protein acetyltransferases containing a GNAT domain can acetylate acetyl-CoA synthetases.…”
Section: Makat Containing Act-gnat Domain Organization Is Amentioning
confidence: 99%
“…In the enteric bacteria E. coli, the transcription of protein acetyltransferase PatZ is controlled at the transcriptional level in response to the intracellular cAMP signal. The catabolite activator protein-cAMP complex binds to two sites in the patZ promoter and induces the expression of genes that increase the level of acetylated proteins (4). The activity of protein acetyltransferases is also controlled by allosteric effects.…”
mentioning
confidence: 99%
“…The enzyme PatZ directly acetylates isocitrate lyase (AceA) and maybe isocitrate dehydrogenase phosphatase (AceK). The expression of patZ is regulated by catabolite repression, while cobB is constitutively expressed [71]. Findings of changing phosphorylation patterns in Mdh, Pck and AcnB contribute to demonstrate the tight mechanism of regulation by post-translational modification in the E. coli central carbon metabolism.…”
Section: Accepted Manuscriptmentioning
confidence: 92%